An exceptionally stable octacobalt-cluster-based metal–organic framework for enhanced water oxidation catalysis - Huang, Ning-Yu (Royal Society of Chemistry, 2019)

(untitled) (Chem Sci)
Extensive efforts have been devoted to developing efficient and durable catalysts for water oxidation. Herein, we report a highly stable metal–organic framework that shows high catalytic activity and durability for electrically driven (an overpotential of 430 mV at 10 mA cm(–2) in neutral aqueous solution) and photodriven (a turnover frequency of 16 s(–1) and 12 000 cycles) water oxidation, representing the best catalyst for water oxidation reported to date. Computational simulation and isotope tracing experiments showed that the μ(4)-OH group of the {Co(8)(μ(4)-OH)(6)} unit participates in the water oxidation reaction to offer an oxygen vacancy site with near-optimal OH(–) adsorption energy.